Effectiveness and safety of recombinant factor VII in pediatric cardiac surgery aged 13 years or less: A meta-analysis - Hanan Abu Hassan; Faisal Rustom; Hend Ali Bafaqih; Reem Mohamed Beheri; Shawana Farooq Shaikh; Sultan Al Dalbhi (International Journal of Health Sciences, 2020)
Objectives: Bleeding is the most serious complication of cardiac surgery among pediatric patients. Recombinant factor VII (rFVII) is a widely used coagulant, despite a lack of evidence on its effectiveness. The current study aimed to summarize the effectiveness and safety of using rFVII in pediatric cardiac surgery using data from existing double-arm studies. Methods: After a systematic search of existing databases and careful scrutiny by two independent researchers, seven double-arm studies were shortlisted. Of these seven studies, there was one randomized control trial, one cohort study, and five case–control studies, which together had 1117 pediatric patients of cardiac surgery. rFVII was administered in the intervention arm group, whereas either a placebo or blood products were given to the control group for bleeding. Pooled risk ratio was the summary measure of association for thrombotic complications, reexploration, and mortality among the two groups. The standard mean difference was calculated for comparing mean chest tube output before and after the administration of rFVII between the two groups using the random-effects model. The heterogeneity coefficient was calculated for each outcome measure. Results: No statistically significant difference was observed for mean chest tube output (before – [mean difference = 3.36, 95% confidence interval (CI) = −0.60, 7.31, P = 0.10] and after – [mean difference = −0.34, 95% CI = −0.26, 2.01, P = 0.78] administering rFVII), thrombotic complications (RR = 1.39, [95%] CI = 0.69–2.81) and mortality (relative risk [RR] = 1.19 [95%] CI = 0.82–1.74). However, the rate of reexploration was 1.86 times more in the intervention arm as compared to the control arm (RR = 1.86 (95%] CI = 1.16–2.98). There were insufficient data for length of stay in intensive care unit and hospital, and volumes of transfused blood for deriving summary measure. Conclusions: The administration of rFVII does not provide any added advantage for bleeding control among pediatric patients of cardiac surgery. However, it increased the rate of reexploration among the intervention arm. However, due to the small sample sizes of the included studies, the results need to be taken cautiously.